Corrosion behaviour of friction stir welded lap joints of 6061-t6 aluminum alloy - Gharavi, Farhad (2014)
Friction stir welding (FSW) process is an emerging ―green‖ solid-state method in which is accepted as a favourable joining method for aluminium alloys and other engineering materials. The joining of metal plates is done at below their melting point temperature and based on a thermo-mechanical action used by a non-consumable welding tool onto metal plates. However, the microstructure of aluminium alloy and chemistry as well as dimension and distribution of the intermetallic particles in the matrix of aluminium alloy may be modified owing to heat generated and severe plastic deformation during the welding process. Accordingly, mechanical and corrosion properties of weldments can be changed after welding as opposed to the parent alloy. In this work, lap-welded joints of 6061-T6 aluminium alloy were produced by FSW, and the influence of process parameters on their welds quality of weldments in terms of welding defects, microstructure, hardness distribution, and tensile properties as well as effective plate thickness (EPT) by applying the rotation speed and welding speed in the range of 900-1200 rpm and 20-60 mm/min, respectively, have been investigated using visual inspection, CT-scan, optical microscopy, scanning electron microscopy (SEM) equipped with energy dispersive x-ray (EDX) facilities, and mechanical test such as microhardness test and lap shear tensile test on the lap-welded joints, as the first and second objectives. The welding results obtained showed that among all the welding conditions, two welding conditions including 1000 rpm–60 mm/min and 900 rpm-40 mm/min were acceptable and desirable weldments with the highest mechanical properties. Thus, corrosion behaviour of acceptable welded lap joints, which was marked as FSLW 1 with 1000 rpm–60 mm/min and FSLW 2 with 900 rpm-40 mm/min welding conditions, has been evaluated as the third objective by potentiodynamic polarization (Tafel and cyclic polarization) and Intergranular corrosion (IGC) tests as well as ex-situ SEM and atomic force microscopy (AFM) examinations. The IGC test results showed that Intergranular corrosion resistance of heat effect zone (HAZ) was poor compared to weld nugget zone (WNZ) in FSLW 1 and FSLW 2 samples. Tafel polarization test revealed that the corrosion resistance of parent alloy (PA) was higher than the weld regions in FSLW 1 and FSLW 2 samples. The PA, WNZ, and HAZ represented similar corrosion potential values after heat treatment (T6). Cyclic polarization test results for both FSLW 1 and FSLW 2 samples were good agreement with the previous results from the Tafel polarization test. Corrosion behaviour of different positions (top and bottom) of weld nugget zone revealed that the corrosion resistance of the top nugget zone was higher than that of bottom and parent alloy in both FSLW 1 and FSLW 2 samples. Finally, from these results, it is found that the welding process has a major effect on corrosion resistance of weld regions, which is attributed to the breaking down and dissolution of intermetallic particles.